NCOG-19. PROGNOSTIC FACTORS IN ELDERLY PATIENTS WITH GLIOBLASTOMA: A RETROSPECTIVE INSTITUTIONAL SERIES OF 160 PATIENTS. (12th November 2021) - Pellerino, Alessia; Bruno, Francesco; Pronello, Edoardo; Mo, Francesca; Franchino, Federica; Rudà, Roberta; Soffietti, Riccardo
Abstract: INTRODUCTION: Glioblastoma (GBM) prevails in elderly patients, who often suffer from other comorbidities that may affect the outcome. The aim of the study was to investigate clinical characteristics, comorbidities, and treatment-related complications that may impact the outcome of elderly patients with GBM. PATIENTS AND METHODS: In this institutional retrospective study, we included GBM patients ≥ 65 years diagnosed with glioblastoma from 2015 to 2020. We retained information about comorbidities according to Charlson Comorbidity Index (CCI), Karnofsky prognostic score (KPS), MGMTp methylation, and clinical complications during treatment or follow-up. RESULTS: We included 160 patients. Median age was 72 years (65-88). Median time of follow-up was 9.25 months. Median progression-free survival (mPFS) and overall survival (mOS) were 5.84 and 9.67 months. In a multivariate analysis, factors affecting survival were: KPS after surgery ≥ 70 (mPFS: HR 0.24, 0.13-0.44; mOS: HR 0.43, 0.24–0.76. 95% CI), partial vs gross total resection (mPFS: HR 2.15, 1.23–3.77; mOS: HR 2.61, 1.34–5.07. 95% CI), MGMTp methylation (mPFS: HR 0.35, 0.22–0.55; mOS: HR 0.37, 0.24–0.76. 95% CI), and complications after surgery (mPFS: HR 2.52, 1.39–4.55; mOS: HR 2.96, 1.63–5.40. 95% CI). Conversely, age and CCI were not significantly correlated with prognosis. CONCLUSIONS: For elderly patients with GBM, CCI does not seem to predict the outcome. Other factors such as extent of surgery, MGMTp methylaton, postoperative KPS, and clinical complications after surgery retain a significant prognostic importance. Further studies are needed to standardize clinical prognostic scales specific for elderly GBM patients.